Diagnosis of Helicobactor pylori in Bangladesh: Limited Options and Utility of Serologic Test (Journal of Shaheed Suhrawardy Medical College, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16195 J Shaheed Suhrawardy Med Coll, 2013;5(1):1-2